The Multilingual Practice in a Rural and Urban Setting in Lombok, Indonesia - Panji Tanashur; Bidari Andaru Widhi; Rosidah Alawiyah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The Sasak tribe is categorized as one of the multilingual speakers that exist in Indonesia who speak Bahasa Indonesia and Sasak Language (SL). The SL has two speech levels: Sasak Jamaq (SJ) for the lower level and Sasak Alus (SA) for the upper one. Along with social considerations, people's multilingual practice may differ from urban and rural settings in the Lombok region. This research aims to investigate the multilingual practice along with the factors that influence language choice in educational, casual conversation, and traditional gatherings domains within both rural and urban areas around Lombok. This research used a descriptive qualitative method employing the ethnographic research approach to collect data. Participants were categorized based on specific events that were taking place such as sorong serah events (traditional gatherings), Car-free days (casual conversations), and educational activities on campus. It turns out that the multilingual practice in the two settings (urban and rural) has the same pattern on how SA is becoming extinct. The linguistic endangerment has been caused by the widespread disregard shown by both non-royal descendants and meritocratic households. Furthermore, the limited domain is accessible for usage as a communication tool due to language policy, which incorporates Bahasa Indonesia in numerous formal contexts and excludes SA from school curricula. Furthermore, the domain is the biggest matter in how they choose a language to communicate as well as the topic, interlocutor identities, social status, and politeness.